Explanatory and Confirmatory Approaches to Curriculum Based on Matthew 28:19: An Analysis of the Content Dimension of Teaching for Theology Lecturers - Elia Umbu Zasa; Hana Suparti; Maria Titik Windarti (Jurnal Pendidikan Agama Kristen (JUPAK), 2026)
Theological education is designed to equip students with the knowledge, competencies, and dispositions necessary for effective ministry. This article situates Matthew 28:19 as the biblical and theological foundation for the content dimension of the curriculum. The dominical command to “make disciples of all nations” underscores the universal and enduring mandate of the church. A linguistic and exegetical analysis of the Greek text demonstrates that the principal verb matheteusate (“make disciples”) is structurally reinforced by the aorist participle poreuthentes (“go”) and further elaborated through the imperatives “baptize” and “teach.” These grammatical features reveal that the content of theological instruction must be oriented toward comprehensive discipleship, integrating both doctrinal formation and practical engagement. The study argues for the development of teaching content that is contextually grounded, missionally relevant, and theologically rooted in the authority of Christ. By placing matheteusate at the center of curricular reflection, the article highlights discipleship as an ongoing, holistic, and universally applicable process encompassing instruction, mentoring, and spiritual accompaniment. Drawing on theological and linguistic perspectives, this study advances the claim that curriculum design in theological education must be intentionally aligned with the Great Commission. Methodologically, the research employs a quantitative approach to examine the explanatory and confirmatory dimensions of curriculum development.